Microbiota-based interventions for autism spectrum disorder: a systematic review of efficacy and clinical potential - Taha, Hana; Issa, Ahmad; Muhanna, Zaid; Al-Shehab, Majdi; Wadi, Tuleen; Awamleh, Suhib; Ateiwi, Yousef A.; Abusido, Mohammad; Berggren, Vanja (Frontiers in Microbiology, 2025)
PurposeAutism spectrum disorder (ASD) is increasingly linked to gut microbiota imbalances, influencing both behavioral and gastrointestinal (GI) symptoms. This systematic review assesses the efficacy of microbiota-based interventions, including probiotics, prebiotics, synbiotics, and fecal microbiota transplantation (FMT), in improving ASD-related symptoms, aiming to provide insights into their therapeutic potential and inform future clinical applications.MethodsA comprehensive systematic review was conducted following PRISMA guidelines and registered in PROSPERO (CRD42024615043). A structured literature search was performed in PubMed, Cochrane Library, and Scopus to identify peer-reviewed English-language studies. Eligible studies included randomized controlled trials (RCTs), non-randomized trials (NRTs), and retrospective studies assessing the impact of microbiota-based interventions on ASD-related behavioral and GI outcomes. Two independent reviewers conducted study selection, data extraction, and quality assessment using standardized risk-of-bias tools.Results33 studies were included, consisting of 16 RCTs, 14 NRTs, and 3 retrospective studies. Among them, 15 assessed probiotics, 4 prebiotics, 5 synbiotics, and 9 FMT. Probiotics showed moderate behavioral improvements in ASD, with multi-strain formulations being more effective than single strains. Prebiotics and synbiotics yielded mixed results, with some studies indicating benefits in behavioral and GI symptoms. FMT demonstrated the most consistent and sustained improvements in both ASD-related behaviors and GI function. Adverse events were minimal, primarily involving transient GI symptoms.ConclusionMicrobiota-targeted interventions, particularly FMT, hold promise for managing ASD symptoms, though probiotics, prebiotics, and synbiotics present variable efficacy. Standardized protocols, larger controlled trials, and personalized microbiome-based approaches are necessary to refine these therapeutic strategies and enhance clinical applicability.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42024615043, identifier CRD42024615043.